MicroRNA-204 Regulates Angiogenesis and Vasculogenic Mimicry in CD44+/CD24− Breast Cancer Stem-like Cells - Martha Resendiz-Hernández; Alejandra P. García-Hernández; Macrina B. Silva-Cázares; Rogelio Coronado-Uribe; Olga N. Hernández-de la Cruz; Lourdes A. Arriaga-Pizano; Jessica L. Prieto-Chávez; Yarely M. Salinas-Vera; Eloisa Ibarra-Sierra; Concepción Ortiz-Martínez; César López-Camarillo (Non-Coding RNA, 2024)
Tumors have high requirements in terms of nutrients and oxygen. Angiogenesis is the classical mechanism for vessel formation. Tumoral vascularization has the function of nourishing the cancer cells to support tumor growth. Vasculogenic mimicry, a novel intratumoral microcirculation system, alludes to the ability of cancer cells to organize in three-dimensional (3D) channel-like architectures. It also supplies the tumors with nutrients and oxygen. Both mechanisms operate in a coordinated way; however, their functions in breast cancer stem-like cells and their regulation by microRNAs remain elusive. In the present study, we investigated the functional role of microRNA-204 (miR-204) on angiogenesis and vasculogenic mimicry in breast cancer stem-like cells. Using flow cytometry assays, we found that 86.1% of MDA-MB-231 and 92% of Hs-578t breast cancer cells showed the CD44+/CD24− immunophenotype representative of cancer stem-like cells (CSCs). The MDA-MB-231 subpopulation of CSCs exhibited the ability to form mammospheres, as expected. Interestingly, we found that the restoration of miR-204 expression in CSCs significantly inhibited the number and size of the mammospheres. Moreover, we found that MDA-MB-231 and Hs-578t CSCs efficiently undergo angiogenesis and hypoxia-induced vasculogenic mimicry in vitro. The transfection of precursor miR-204 in both CSCs was able to impair the angiogenesis in the HUVEC cell model, which was observed as a diminution in the number of polygons and sprouting cells. Remarkably, miR-204 mimics also resulted in the inhibition of vasculogenic mimicry formation in MDA-MB-231 and Hs-578t CSCs, with a significant reduction in the number of channel-like structures and branch points. Mechanistically, the effects of miR-204 were associated with a diminution of pro-angiogenic VEGFA and β-catenin protein levels. In conclusion, our findings indicated that miR-204 abrogates the angiogenesis and vasculogenic mimicry development in breast cancer stem-like cells, suggesting that it could be a potential tool for breast cancer intervention based on microRNA replacement therapies.